Outcast and Life of a Transgender in I am Vidya: A Transgender’s Journey (International Journal of Food and Nutritional Sciences, 2022)
In the current scenario, after the Supreme Court‘s historical judgement, a new kind of literature i.e., hijra literature is emerging in Indian literary academia. Many hijras are participating in writing and exploring the crucial phases through which they are moving after the declination of the Mughal period. They are actively and skillfully using this platform to revise their lost social recognition. They justify their existence through revising history and myths. The problem of gender and gender identity is perhaps the most discussed issues in the present literary academia. Judith Butler through her oft quoted book Gender Trouble: Feminism and Subversion of Identity, made perhaps the largest contribution in gender discourse and explored the idea that gender is a social construct and enforced through social practice.